GLCS' performance in Malaysia does corruption matters - Catherine Ann, Mariadass; Choy, Chun Yin; Leong, Yue Ven; Yeap, Xin Wei (2021)
The primary aim of conducting this research is to determine the factors that influence the performance of GLCs in Malaysia, especially to shed light on the impacts of corruption towards GLCs’ performance as it is commonly known that bribery is often times inevitable when it comes to the dealings with government authorities. This research is carried out using secondary data collected from 2013 to 2019, annually on 24 GLCs in Malaysia. Difference GMM estimation approach is utilised to evaluate the relationship between the independent variables and the dependent variable. The empirical test result showed that GDP, corruption and state ownership have significant impact on the performance of GLCs while financial leverage showed no significant influence on GLCs’ performance in Malaysia. The limitations and recommendations of the study are provided to benefit future researchers as well as to those who will find results of this study useful.